Dynamics of dissolved organic carbon and total dissolved nitrogen in Maryland's coastal bays. (5th October 2015) - Duan, Shuiwang; Chen, Nianhong; Kaushal, Sujay S.; Chigbu, Paulinus; Ishaque, Ali; May, Eric; Oseji, Ozuem F.
Abstract: Dissolved organic matter (DOM) provides nutrients and energy subsidies for harmful algal blooms in Maryland's Coastal Bays (MCBs, USA). The composition, sources and dynamics of DOM in MCBs are not well known. In this study, dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) were monitored monthly over a period of one year (July 2011 to June 2012) at 13 stations in the MCBs. Absorption and fluorescence spectroscopy were used to characterize DOM composition and track terrestrial inputs versus aquatic sources of DOM. Results show that DOC and TDN concentrations in the MCBs (187–501 μM and 19.4–40.6 μM) were comparable to eutrophic coastal waters in the United States but much higher than the mid-Atlantic Bight. This suggests that the MCBs are a DOM source for the coastal ocean. Spatially, nearshore sites had relatively higher DOC and TDN concentrations and terrestrially-derived aromatic DOM (indicated by high humification index) than the bays that were directly connected to the Atlantic Ocean. Seasonally, DOC from the main body of the MCBs (Chincoteague and Assawoman Bays) displayed a pronounced seasonal pattern with the highest values occurring in summer. Protein-like DOM from algal/bacterial inputs (indicated by high biological freshness index or fluorescence index) was also highest in summer but then decreased gradually until April. DOC concentrations at the nearshore site were highest in later spring, probably due to terrestrial inputs. Conversely, TDN concentrations in smaller bays with faster flushing rates (Newport, Sinepuxent and Isle of Wight Bays) were highest in April, probably due to watershed nitrogen inputs. This spring TDN peak was not apparent in the main body of the MCBs, which have longer flushing times (indicating stronger biological nitrogen uptake). This study suggests that DOM in eutrophic, shallow coastal bays such as the MCBs consists of a large fraction of protein-like components from local algal/microbial sources during summer. This enhanced primary productivity is likely fueled by watershed nitrogen inputs from agricultural and urban land use during spring. Further insights regarding spatiotemporal variations and controls of DOM abundance, composition and sources in the MCBs can be helpful in guiding and prioritizing coastal restoration efforts for reducing eutrophication and water quality degradation.